2006
DOI: 10.1128/iai.74.5.3052-3059.2006
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Histidine Kinases HP0165 and HP1364 for Acid Resistance in Helicobacter pylori

Abstract: In this study, we investigated a potential requirement of two-component signal transduction systems for acid resistance in Helicobacter pylori. In comparison to a wild-type strain, isogenic strains with null mutations in either HP0165 or HP1364 histidine kinases were impaired in their ability to grow at pH 5.0. The growth of complemented mutant strains was similar to that of the wild-type strain. H. pylori DNA array analyses and transcriptional reporter assays indicated that acid-responsive gene transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 43 publications
(71 reference statements)
2
53
0
Order By: Relevance
“…Extraction of RNA was done using the Trizol method (Invitrogen), and the extracted RNA was further purified with RNeasy spin columns (Qiagen). Labeling of RNA with [ 33 P]dATP was carried out with SuperScript II Reverse Transcriptase (Invitrogen) as described previously (20). Each labeled RNA preparation was then hybridized to H. pylori Panorama arrays (Sigma Genosys) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of RNA was done using the Trizol method (Invitrogen), and the extracted RNA was further purified with RNeasy spin columns (Qiagen). Labeling of RNA with [ 33 P]dATP was carried out with SuperScript II Reverse Transcriptase (Invitrogen) as described previously (20). Each labeled RNA preparation was then hybridized to H. pylori Panorama arrays (Sigma Genosys) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmids containing the cat cassette in the desired orientation were identified by PCR. The plasmid used for construction of the ureA-cat transcriptional fusion has been described previously (20). H. pylori reporter strains were generated by transformation of H. pylori strain 26695 SC#7 with the plasmids described above, and transformants were selected on BB-FBS-0.5% agar plates containing 5 Ag/mL chloramphenicol.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence supporting a cognate relationship between ArsS and ArsR includes immediate proximity of the two genes in the H. pylori chromosome and the demonstration that the two purified proteins can participate in a phosphotransfer reaction in vitro (12). H. pylori ArsS null mutants are viable, but such mutants are impaired in the ability to grow in low pH in vitro, and these mutant strains are unable to colonize mice (14,15). Attempts to generate ArsR null mutants have been unsuccessful, which suggests that ArsR is essential for H. pylori viability (12).…”
mentioning
confidence: 99%
“…Several recent studies reported that an H. pylori TCS, ArsSArsR (acid-responsive signaling sensor/response regulator), responds to acidic conditions (12)(13)(14)(15)(16)(17)(18)(19)(20). This TCS consists of the histidine kinase protein, ArsS, and the RR protein, ArsR.…”
mentioning
confidence: 99%
See 1 more Smart Citation